The Influence of Education Level on Community Migration Patterns in Border Areas - Dhiyaulhaq, Rafif Allaam (Muhammadiyah University of Makassar, 2026)
Inequalities in access to education in border regions remain a challenge that can affect population mobility and regional development dynamics. Limited infrastructure, a shortage of teaching staff, and the uneven distribution of learning facilities make it difficult for communities to obtain adequate educational services in their home regions. This study aims to identify the relationship between educational attainment and population mobility in border regions, analyze the educational factors driving migration, and explain the mobility patterns resulting from disparities in educational access across regions. The method employed is a literature review of seven primary sources selected based on publication period, credibility, and topic relevance. The analysis was conducted thematically and descriptively. The results indicate that limited access to education serves as a push factor, while the availability of facilities and social support in the destination region act as pull factors, with mobility patterns that can be either internal or cross-border. The study recommends strengthening educational facilities, scholarships, and cross-border partnerships as strategies for managing mobility.